Attractions, attitude, and activities: Tourism attributes that drive destination loyalty for international tourists visiting Thailand - Viriya Taecharungroj (2018)
Copyright © 2017 Inderscience Enterprises Ltd. The purposes of this research are to develop a destination loyalty model that employs the attribute-level satisfaction approach and to study the characteristics of those key tourism attributes in Thailand in order to suggest practical guidelines for tourism policymakers and destination managers. To study the impacts of various tourism attributes on destination satisfaction and loyalty, data were collected from 525 international tourists in Bangkok, Thailand. The hypotheses were tested using structural equation modelling. The authors also conducted in-depth interviews with tourism policymakers and international tourists to deepen the understanding of the key tourism attributes and to investigate areas for improvement. The findings show that three attributes - attractions, locals' attitude, and activities - significantly affect overall destination satisfaction and destination loyalty. This research also revealed areas for improvement in the tourism sector, namely sustainability issues, commercialism, and a lack of information.